Effect of Food on the Bioavailability of Omadacycline in Healthy Participants - Tzanis, Evan (J Clin Pharmacol, 2016)
Omadacycline is a first‐in‐class aminomethylcycline antibiotic being evaluated in phase 3 studies as oral and intravenous monotherapy for bacterial infections. This was a phase 1, randomized, open‐label, 4‐period, crossover study that evaluated the effect of food consumption on the bioavailability of omadacycline. Healthy participant were randomized to 1 of 4 sequences, which included the following predose conditions in different orders (A) ≥6‐hour fast, (B) high‐fat, nondairy meal 4 hours before dosing, (C) high‐fat, nondairy meal 2 hours before dosing, and (D) high‐fat meal containing dairy 2 hours before dosing. Participants received a single 300‐mg oral dose of omadacycline during each treatment period; periods were separated by ≥5 days. Blood samples for pharmacokinetic (PK) analysis were collected over 24 hours after each dose, and safety assessments were performed during each treatment period. Least‐squares mean and 90% confidence intervals were compared for fed state vs fasted state. Thirty‐one participants were included in the PK analysis. Fasted AUC(0‐∞), AUC(0‐t), and AUC(0‐24) were 10.2, 7.2, and 7.2 μg·h/mL, respectively, and C(max) was 0.6 μg/mL. Compared with a fasted dose, bioavailability was reduced by 15% to 17% by a nondairy meal 4 hours before dosing, 40% to 42% by a nondairy meal 2 hours before dosing, and 59% to 63% for a dairy meal 2 hours before dosing. Two participants experienced adverse events (mild nausea, mild somnolence). A 300‐mg oral dose of omadacycline administered within 2 to 4 hours after food had reduced bioavailability compared with the fasted state. Oral omadacycline should be administered in a fasted state.